2008
DOI: 10.1093/ajcn/87.3.593
|View full text |Cite
|
Sign up to set email alerts
|

Study of the effect of trans fatty acids from ruminants on blood lipids and other risk factors for cardiovascular disease

Abstract: Background:The intake of trans fatty acids (TFA) from industrially hydrogenated vegetable oils (iTFA) is known to have a deleterious effect on cardiovascular health, the effects of TFA from ruminants (rTFA) are virtually unknown. Objective: The purpose of the present study was to compare the effects of rTFA and iTFA on plasma LDL concentrations and other cardiovascular disease risk factors in healthy subjects. Design: In a double-blind, randomized crossover controlled study, 38 healthy men were fed each of 4 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
149
5
8

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(169 citation statements)
references
References 32 publications
7
149
5
8
Order By: Relevance
“…Three recent studies attempted to determine whether trans fats from these two sources had different effects on plasma lipids and lipoproteins (28)(29)(30). The first of these studies by Motard-Belanger and colleagues (29) determined that diets enriched in either natural or commercial trans fats had similar effects on HDL and LDL cholesterol, as well as on the total cholesterol:HDL cholesterol ratio. In the TRANSFACT study (28), a statistically significant decrease in both HDL and LDL cholesterol was observed in women consuming commercial but not natural trans fat; no change was seen in men.…”
Section: Industrial Vs Natural Trans Fatmentioning
confidence: 99%
“…Three recent studies attempted to determine whether trans fats from these two sources had different effects on plasma lipids and lipoproteins (28)(29)(30). The first of these studies by Motard-Belanger and colleagues (29) determined that diets enriched in either natural or commercial trans fats had similar effects on HDL and LDL cholesterol, as well as on the total cholesterol:HDL cholesterol ratio. In the TRANSFACT study (28), a statistically significant decrease in both HDL and LDL cholesterol was observed in women consuming commercial but not natural trans fat; no change was seen in men.…”
Section: Industrial Vs Natural Trans Fatmentioning
confidence: 99%
“…The effects of ruminant-derived trans FA on human health have yet to be fully clarified -the isomer profile of ruminant products is different from that of industrial trans FA. Recently, Motard-Bé langer et al (2008) suggested that moderate intakes of ruminant-derived trans FA are unlikely to have negative effects on cardiovascular disease risk factors, but until any isomer-specific effects are documented increased amounts of trans FA in milk should be viewed with caution.…”
Section: --mentioning
confidence: 99%
“…intake of industrial TFA has a deleterious effect on lipoprotein concentrations; however, ruminant TFA may be less detrimental to blood lipid levels than industrial TFA (10) . Two isomers of CLA are cis-9, trans-11 (c9,t11) and trans-10, cis-12 (t10,c12) (11)(12)(13)(14)(15)(16)(17) .…”
mentioning
confidence: 99%